A Bioinspired Adaptive Congestion-Avoidance Routing for Mobile Ad Hoc Networks. (14th May 2014) - Qiong, Huang; Pengfei, Yin; Qianbin, Chen; Pu, Gong; Xiaolong, Yang
Abstract : Traditional mobile Ad Hoc network routing protocols are mainly based on the Shortest Path, which possibly results in many congestion nodes that incur routing instability and rerouting. To mitigate the side-efforts, this paper proposed a new bioinspired adaptive routing protocol (ATAR) based on a mathematics biology model ARAS. This paper improved the ARAS by reducing the randomness and by introducing a new routing-decision metric "the next-hop fitness" which was denoted as the congestion level of node and the length of routing path. In the route maintenance, the nodes decide to forward the data to next node according to a threshold value of the fitness. In the recovery phase, the node will adopt random manner to select the neighbor as the next hop by calculation of the improved ARAS. With this route mechanism, the ATAR could adaptively circumvent the congestion nodes and the rerouting action is taken in advance. Theoretical analysis and numerical simulation results show that the ATAR protocol outperforms AODV and MARAS in terms of delivery ratio, ETE delay, and the complexity. In particular, ATAR can efficiently mitigate the congestion.